Microbiological pattern of laboratory confirmed vaginal infections among Saudi women - Dalia Saad ElFeky; Rasha Assiri; Hanadi Bakhsh; Ruba Almubaraz; Afrah Aldhowayan; Shahad Ismail Alruwaili; Raghad Alomairy (IMR Press, 2021)
Background: Imbalance in vaginal microbiota causes vaginal infection in women in mainly reproductive age. This study aimed to determine the microbiological and epidemiological profile of laboratory confirmed vaginal infections among Saudi women. Methods: This cross-sectional retrospective study involved medical records of Saudi women patients with laboratory confirmed vaginal infections from a private hospital in Riyadh, Saudi Arabia between January 2015 and January 2019. Results: Among the 4300 medical records that were reviewed, 564 (13.1%) had laboratory-confirmed vaginal infections. Data was collected about participant's personal and social data, medical history, primary presenting symptom, associated symptoms, obstetric and gynecological history, results of vaginal examination, the results of microbiological tests of vaginal swab specimens, and treatment given, using a data sheet. Sample collected were examined for bacterial vaginosis (BV), Vulvovaginal candidiasis (VVC), trichomonal vaginitis (TV), Group B Streptococcus (GBS) and other infections. Data was analyzed using SPSS version 21. VVC was the most common type (57.4%) followed by GBS (25%) and BV (12.1%). Vaginal infections were found to be associated with reproductive age group and high BMI. Most of the included patients did not have classic risk factors for vaginal infections. Discussion: The medical records of 564 patients, all with laboratory-confirmed vaginal infections were included in this study, which represents 13.1% of all patients who had attended the clinic during the study period. The mean age of the participants in this study was 40.97 ± 8.5 years.